Mobilizing the Spiritual Resources of the Nation: The 1918 United War Work Campaign - Petit, Jeanne (Church history, 2022)
On September 3, 1918, President Woodrow Wilson released a letter praising organizations that had provided services for soldiers, including the Young Men's Christian Association, the National Catholic War Council, and the Jewish Welfare Board. Through the work of these groups, the president declared, "the moral and spiritual resources of the nation have been mobilized." Wilson then asked that, instead of the individual fundraising drives they were planning, the groups instead have single drive during the week of November 11, 1918, what he called a "united war work campaign."The United War Work Campaign provides a window into understanding how a more pluralistic United States emerged through a process that involved competition and sacrifice as well as cooperation. The YMCA leadership fought to have a separate campaign, but they were forced into accommodating the changing religious dynamics of the nation. The Catholic and Jewish groups confronted Protestant establishment assumptions as they offered their own takes on how to appeal to a diverse American public. All the religious groups found themselves in situations where they had to downplay their faith commitments to ensure the campaign's success, and this led to tensions within the organizations and struggles with their co-religionists. Overall, the United War Work revealed the challenges of church-state collaboration and the compromises that were necessary for the emergence of a tri-faith nation.